Studies on the property of membrance surface influence on ultrafiltration separating protein - QIAN Jun-qing (浙江大学学报. 农业与生命科学版, 2000)
The variation of close water ultrafiltration membrance and detest water ultrafiltration cuting off protein is investigated by changing the pH and ratio of water to ethanol in the water solution of protein. Influences of the membrance surface property on the separation of protein is expressed by ratio of cutting off. The results show that the polarity of membrance surface and electric property of proptein and absorption layer of protein influence separation of protein is remarkable.